2019
DOI: 10.1088/1361-6455/ab4eef
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of functionals in density functional theory by the inverse Kohn–Sham method and density functional perturbation theory

Abstract: We propose a way to improve energy density functionals (EDFs) in the density functional theory based on the combination of the inverse Kohn-Sham method and the density functional perturbation theory. Difference between the known EDF and the exact one is treated as the first-order perturbation. As benchmark calculations, we reproduce the theoretical exchange and correlation functionals in the local density approximation. Systems of noble-gas atoms are used for benchmark calculations, and the ground-state energi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 118 publications
1
20
0
Order By: Relevance
“…To make a link to microscopic approaches of EDFs, ab initio determination of such parameters is highly motivated [2,[18][19][20][21][22][23][24][25][26][27]. To attain such a goal, novel methods using functional renormalization group [28][29][30][31][32][33][34][35][36] and inverse Kohn-Sham method [37][38][39] have also been proposed, although these attempts are still limited.…”
mentioning
confidence: 99%
“…To make a link to microscopic approaches of EDFs, ab initio determination of such parameters is highly motivated [2,[18][19][20][21][22][23][24][25][26][27]. To attain such a goal, novel methods using functional renormalization group [28][29][30][31][32][33][34][35][36] and inverse Kohn-Sham method [37][38][39] have also been proposed, although these attempts are still limited.…”
mentioning
confidence: 99%
“…The basic idea is that the physical properties of the ground state of atoms, molecules and solids can be described by the particle number density function, and the ground state of the system is the state in which the energy functional takes the minimum value under the condition of constant particle number. [11,12] This not only provides a theoretical basis for simplifying the multi-electron problem into a single electron problem but also does not need to rely on any empirical parameters. The atomic and electronic structures and related physical properties of materials can be obtained by solving the intrinsic quantum mechanical equations.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9]. This topic has recently encountered a renewed interest both in quantum chemistry [10][11][12][13][14] and in nuclear physics [15,16] (our group had undertaken preliminary steps before Ref. [15], cf.…”
Section: Introductionmentioning
confidence: 99%
“…[22] it has been shown that training a neural network EDF not only on energies, but also on potentials, greatly improves its performances, at least in a simplified one-dimensional framework. A different line of research combines density functional perturbation theory (DFPT), where an ansatz for the EDF functional form must be assumed, and IKS to improve the initial model towards the exact EDF [11,16]. Illustrative calculations have been performed in the case of covariant nuclear DFT [16].…”
Section: Introductionmentioning
confidence: 99%